Analisis Gaya Kepemimpinan B.J. Habibie Sebagai Presiden Pada Masa Transisi Demokrasi - Khoirulloh, Rofiq Wahyuda; Fahruddin, Fahruddin (Jurnal Politikom Indonesiana, 2024)
As a president who took office in a situation and condition that was still unstable, the vision of reform became a heavy responsibility for B. J. Habibie. In the midst of economic downturn and political instability, Habibie was faced with the demand to move quickly in making policies and decisions that had a significant impact on society. In addition, he also needed to determine the type of leadership style he would apply during his presidency. The transformative leadership style is very relevant to the reform ideals to be achieved. The implementation of the leadership style applied by Habibie resulted in a series of policies and decisions, ranging from those that had a positive impact to those that were controversial. This research adopts a literature study approach using descriptive analysis techniques. The author describes the results of the analysis taken from various sources to reach conclusions that are in accordance with the research needs. In addition, the author also applies systematic analysis techniques to understand the content of the implied message so that it can be explained precisely and accurately. The research results produced through analysis by the author show that B. J. Habibie used a transformational leadership style that was in line with the ideals of reform. He succeeded in taking various transformative policies and decisions in various sectors. Although the policies taken were inseparable from the controversies that arose due to the leadership style applied, the leadership style proved to be effective and well implemented at that time, even providing long-term impacts until today. Keywords: B.J. Habibie, Democratic Transition, Leadership Style, Transformative